THE EFFECT OF WARM RED GINGER COMPRESSES ON JOINT PAIN IN THE ELDERLY WITH GOUT - Erni Tri Indarti; Lexy Oktora Wilda; Erika Septiya Wulansari (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
The elderly go through the aging process, which will lose resistance to infection with the accumulation of degenerative diseases and also the accumulation of uric acid. The elderly with increased uric acid will experience repeated joint pain due to the precipitate of monosodium urate crystals accumulated in the joints. One of the treatments of joint pain in addition to pharmacological therapy there are also non-pharmacological therapies that can reduce side effects, affordable, easy to get and easy to do, namely one of the natural ingredients that are suitable for causing warm sensations, one of which is red ginger. Red ginger reduces pain due to the content of gingerol and shangoal which add heat to warm compresses, besides that the skilooginase content in red ginger is able to inhibit prostaglandins to deliver pain. The purpose of this research to knowing the effect of red ginger warm compresses on changes in joint pain in elderly with gout. This research is a pre-experimental research with One-Group Pre-Post test design approach. The study was conducted in 20 people with the total sampling technique in the Posyandu for the Elderly of Bagor Kulon Villageor 3 days. Measurement of the pain was VAS was given before and after the patients were given warm red ginger compresses. The data was analyzed SPSS 21 Paired Samples test. The Statistical test results obtained p value 0.000 so there is an Effect of Red Ginger Warm Compresses On changes in Joint pain in elderly gout. Red ginger warm compresses can be used as a non-pharmacological therapy in reducing gouty arthritis in the elderly.